Analysis Of The Bankometer Method In Predicting Financial Distress At PT. Bank Muamalat Indonesia - Hafiza, Dara; Rahma, Tri Inda Fadhila; Harahap, Rahmat Daim (Universitas Labuhanbatu, 2024)
This study aims to determine the soundness level of Islamic bank at PT. Bank Muamalat Indonesian to use the Bankomenter method in accordance with POJK No.8/POJK.03/2014 concerning Soundness level of sharia commercial banks and sharia business units. This study use a qualitative approach methode. The data studied is qualitative data sourced from secondary data, namely from the 2015-2020 financial report. Data collection techniques and instruments using literature studies and decomentation studies. Data analysis used to find out how soundness level of a bank in this study is descriptive analysis using Bankometermethode. The result of this research shows the soundness level of the bank at PT. Bank Muamalat Indonesian in 2015-2020 is in Composite Rating 2 (PK-2) in the â€œHealthyâ€ category. This reflects significant bank conditions and changes in business conditions as well as other external factors and if weaknesses are found, in general these weaknesses are quality significant which if not handled properly by management can distrupt the continuity of banks business including loss of public trust at the bank.Â